The macrophage activation marker sCD163 is associated with changes in NAFLD and metabolic profile during lifestyle intervention in obese children. Issue 3 (30th July 2014) - Kazankov, K.; Møller, H. J.; Lange, A.; Birkebæk, N. H.; Holland‐Fischer, P.; Solvig, J.; Hørlyck, A.; Kristensen, K.; Rittig, S.; Handberg, A.; Vilstrup, H.; Grønbæk, H.
Summary Background Obesity is associated with metabolic derangement and non‐alcoholic fatty liver disease (NAFLD). Macrophages are involved in liver inflammation and fibrosis, and soluble (s)CD163 is a macrophage activation marker. Objectives To associate sCD163 with parameters of paediatric obesity and NAFLD, as well as changes in these parameters during lifestyle intervention. Methods We studied 117 obese children during a 10‐week lifestyle intervention; 71 completed the 12‐month follow‐up. We recorded clinical and biochemical data, and performed liver ultrasonography. Results Baseline sCD163 was higher in children with elevated alanine transaminase (ALT) (2.3 ± 0.7 vs. 2.0 ± 0.6 mg L−1, P = 0.03), steatosis (2.3 ± 0.7 vs. 2.0 ± 0.6 mg L−1, P = 0.01) and high paediatric NAFLD fibrosis index (2.3 ± 0.7 vs. 1.9 ± 0.6 mg L−1, P = 0.03). Baseline sCD163 was independently associated with ALT, cholesterol and high‐sensitivity C‐reactive protein (hs‐CRP). The change in sCD163 during lifestyle intervention was associated with changes in ALT, homeostatic model assessment of insulin resistance (HOMA‐IR), hs‐CRP and cholesterol, and inversely associated with the change in high‐density lipoprotein cholesterol. Conclusion sCD163 was associated with markers of liver injury and metabolic parameters in obese children, and changes in these parameters during lifestyle intervention. This may suggest that activated macrophages play a role in NAFLD and sCD163 may serve as a marker of liver disease severity and treatment effect.